Cost-Volume-Profit Analysis and Linear Programming as Profit Planning Instruments - Ana Wijayanti; Bambang Mulyatno Setiawan; Edy Prasetyo (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
This study aimed to analyze the amount of costs, production volume, revenue, and business profit of CV Tani Subur and analyze the BEP and optimize the use of resources in organic fertilizer production in CV Tani Subur to produce maximum profit. The study was conducted in December 2019 at CV Tani Subur, Sleman. The research method used was quantitative method with cost-volume profit and linear programming data analysis. The results showed cost-volume profit analysis is unsuitable to be used in CV Tani Subur profit planning. The re- event point of CV Tani Subur in 2017 had the highest value and caused losses to CV Tani Subur due to its inability to break even. Furthermore, the analysis of linear programming in CV Tani Subur shows that the company will get optimal results if it only produces cow organic fertilizer as much as 548.3925 tons per year. The advantage achieved if producing organic cow fertilizer which is calculated by calculating the simplex method using POM Quantitative methods for windows version 3 software is IDR. 248,392,500 per year.